Successful immunotherapy of autoimmune cholangitis by adoptive transfer of forkhead box protein 3+ regulatory T cells. (November 2014) - Tanaka, H.; Zhang, W.; Yang, G.‐X.; Ando, Y.; Tomiyama, T.; Tsuneyama, K.; Leung, P.; Coppel, R. L.; Ansari, A. A.; Lian, Z. X.; Ridgway, W. M.; Joh, T.; et al.
Summary Treatment of primary biliary cirrhosis (PBC) has lagged behind that of other autoimmune diseases. In this study we have addressed the potential utility of immunotherapy using regulatory T cells (Treg) to treat murine autoimmune cholangitis. In particular, we have taken advantage of our ability to produce portal inflammation and bile duct cell loss by transfer of CD8+ T cells from the dominant negative form of transforming growth factor beta receptor type II (dnTGF‐βRII) mice to recombination‐activating gene (Rag)1–/– recipients. We then used this robust established adoptive transfer system and co‐transferred CD8+ T cells from dnTGF‐βRII mice with either C57BL/6 or dnTGF‐βRII forkhead box protein 3 (FoxP3+) T cells. Recipient mice were monitored for histology, including portal inflammation and intralobular biliary cell damage, and also included a study of the phenotypical changes in recipient lymphoid populations and local and systemic cytokine production. Importantly, we report herein that adoptive transfer of Treg from C57BL/6 but not dnTGF‐βRII mice significantly reduced the pathology of autoimmune cholangitis, including decreased portal inflammation and bile duct damage as well as down‐regulation of the secondary inflammatory response. Further, to define the mechanism of action that explains the differential ability of C57BL/6 Tregversus dnTGF‐βRII Treg on the ability to down‐regulate autoimmune cholangitis, we noted significant differential expression of glycoprotein A repetitions predominant (GARP), CD73, CD101 and CD103 and a functionally significant increase in interleukin (IL)‐10 in Treg from C57BL/6 compared to dnTGF‐βRII mice. Our data reflect the therapeutic potential of wild‐type CD4+ FoxP3+ Treg in reducing the excessive T cell responses of autoimmune cholangitis, which has significance for the potential immunotherapy of PBC.